The Role of Soft Skills in Improving Human Resource Performance and Productivity - Soelistya, Djoko (MSJ : Majority Science Journal, 2025)
This study aims to analyze the role of soft skills in improving the performance and productivity of human resources (HR). The method used in this study is the Systematic Literature Review (SLR), which aims to identify, analyze, and formulate research questions around the influence of soft skills on HR performance and productivity. The first step in SLR is the identification and formulation of research questions, which aim to determine the focus of the study. Based on the results of the study, it can be concluded that soft skills have a significant influence on improving HR performance and productivity. Skills such as communication, teamwork, leadership, and time management have been shown to contribute greatly to work efficiency and effectiveness which in turn have a positive impact on organizational performance. Therefore, the development of soft skills must be an integral part of HR training and development programs in every company. Effective soft skills development requires a holistic approach, where companies not only provide training but also create a work environment that supports the application of these skills.